2005
DOI: 10.1016/j.molcel.2004.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Raf-1 by Direct Feedback Phosphorylation

Abstract: The Raf-1 kinase is an important signaling molecule, functioning in the Ras pathway to transmit mitogenic, differentiative, and oncogenic signals to the downstream kinases MEK and ERK. Because of its integral role in cell signaling, Raf-1 activity must be precisely controlled. Previous studies have shown that phosphorylation is required for Raf-1 activation, and here, we identify six phosphorylation sites that contribute to the downregulation of Raf-1 after mitogen stimulation. Five of the identified sites are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
471
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 554 publications
(496 citation statements)
references
References 42 publications
23
471
0
2
Order By: Relevance
“…Our present findings are in agreement with these previous reports offering a positive role of MEK and ERK in Raf-1 regulation. More recently, after the initial submission of this manuscript, two groups reported Raf-1 phosphorylation on similar sites as reported here (Dougherty et al, 2005;Hekman et al, 2005). Both studies proposed a negative regulatory role for the identified phosphorylations sites in Raf-1 regulation, leading to the enticing hypothesis that ERK participates in a negative feedback loop responsible for down-regulating Raf-1 activity (Dumaz and Marais, 2005).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our present findings are in agreement with these previous reports offering a positive role of MEK and ERK in Raf-1 regulation. More recently, after the initial submission of this manuscript, two groups reported Raf-1 phosphorylation on similar sites as reported here (Dougherty et al, 2005;Hekman et al, 2005). Both studies proposed a negative regulatory role for the identified phosphorylations sites in Raf-1 regulation, leading to the enticing hypothesis that ERK participates in a negative feedback loop responsible for down-regulating Raf-1 activity (Dumaz and Marais, 2005).…”
Section: Discussionsupporting
confidence: 64%
“…Our data, in contrast to the authors claims that this site is regulated downstream of ERK, show little or no change in S43 phosphorylation in the MEK inhibitor-treated cells, whereas resulting in a complete block of the ERK-induced sites (Figure 3). In addition, in our experiments, we did not observe an increase in the Raf-1 activation kinetics in MEK-inhibited cells ( Figure 6B) as observed by Dougherty et al (2005); however, we used COS-7 cells and EGF as stimulus, whereas Dougherty et al (2005) used NIH 3T3 cells and PDGF stimulation. Although remotely likely, it remains a possibility that the differences in our results regarding this specific observation are cell type/mitogen dependent.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Additionally, impairment of ras activity hinders raf activation. 6,[9][10][11] Aberrant activation of this pathway is frequently linked with tumor progression and malignancy, which can contribute to the low efficacy of chemotherapy in patients. 6 Mutations leading to constitutive activation of ras have been found in approximately 30% of all human cancers.…”
Section: Introductionmentioning
confidence: 99%